2023
DOI: 10.1101/2023.02.03.527007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correspondence between functional scores from deep mutational scans and predicted effects on protein stability

Abstract: Many methodologically diverse computational methods have been applied to the growing challenge of predicting and interpreting the effects of protein variants. As many pathogenic mutations have a perturbing effect on protein stability or intermolecular interactions, one highly interpretable approach is to use protein structural information to model the physical impacts of variants and predict their likely effects on protein stability and interactions. Previous efforts have assessed the accuracy of stability pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…Finally, we modelled the effects on protein stability by using FoldX 45 to calculate ΔΔG values for all mutations. Previous work has demonstrated that FoldX outperforms other stability predictors in the identification of disease mutations 46 and shows higher correlations with deep mutational scanning data 47 , providing insights into the molecular mechanisms underlying pathogenic and cancer-associated mutations 23,28 . Because FoldX tends to occasionally output extreme outlier ΔΔG values, and because different proteins can have different intrinsic propensities for destabilising mutations, we introduced a rank normalised metric we call ΔΔG rank for easier visualisation and comparison between proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we modelled the effects on protein stability by using FoldX 45 to calculate ΔΔG values for all mutations. Previous work has demonstrated that FoldX outperforms other stability predictors in the identification of disease mutations 46 and shows higher correlations with deep mutational scanning data 47 , providing insights into the molecular mechanisms underlying pathogenic and cancer-associated mutations 23,28 . Because FoldX tends to occasionally output extreme outlier ΔΔG values, and because different proteins can have different intrinsic propensities for destabilising mutations, we introduced a rank normalised metric we call ΔΔG rank for easier visualisation and comparison between proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in the absence of any selection, an average ΔΔG rank value of around 0.5 would be expected for a set of random mutations. For the PDB structures, we compute the ΔΔG rank using full complex structures, when available, as the inclusion of intermolecular interactions considerably improves the explanatory value of ΔΔG values 23,47 . For AlphaFold models, we can only evaluate the impact of missense mutations in protein monomers.…”
Section: Cancer-associated Missense Mutations Are Enriched For Struct...mentioning
confidence: 99%
“…A summary of the new VEPs assessed in our benchmark along with their sources is provided in Table 2 , while the full list of VEPs is available in Table EV4 . We did not include any methods focussed on predicting the effects of variants on protein stability, but several of these have been assessed in a recent study (preprint: Gerasimavicius et al , 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the MSA-based model, we selected GEMME ( Laine et al, 2019 ), which has been shown to produce state-of-the-art results for protein activity prediction outperforming most current machine learning methods using a relatively simple evolutionary model ( Notin et al, 2022a ). For the structure-based model, we selected stability predictions using Rosetta ( Park et al, 2016 ), which are commonly used within protein engineering and have been shown to make useful predictions of protein stability and abundance ( Frenz et al, 2020; Høie et al, 2022; Gerasimavicius et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%